2024
DOI: 10.1002/ctm2.1587
|View full text |Cite
|
Sign up to set email alerts
|

Sulfotransferase SULT2B1 facilitates colon cancer metastasis by promoting SCD1‐mediated lipid metabolism

Gang Che,
Wankun Wang,
Jiawei Wang
et al.

Abstract: Metastasis is responsible for at least 90% of colon cancer (CC)‐related deaths. Lipid metabolism is a critical factor in cancer metastasis, yet the underlying mechanism requires further investigation. Herein, through the utilisation of single‐cell sequencing and proteomics, we identified sulfotransferase SULT2B1 as a novel metastatic tumour marker of CC, which was associated with poor prognosis. CC orthotopic model and in vitro assays showed that SULT2B1 promoted lipid metabolism and metastasis. Moreover, SULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Using the feature-selection procedure given in METHODS, we identified 11 enzyme genes for the binary classification problem and 14 enzyme genes for the ternary problem. It is noteworthy that all the 11 genes have literature support, showing that they each are associated with metastasis [17,18,19,20]. For the 14 genes, our functional analyses have revealed that they are mainly involved in sex hormone and xenobiotic metabolism, which makes sense as we have discovered that metastasized cancers have considerably elevated cholesterol metabolisms, leading to the production of sex hormones as well as mineral-and glucocorticoid (manuscript in preparation).…”
Section: Feature Selectionmentioning
confidence: 79%
“…Using the feature-selection procedure given in METHODS, we identified 11 enzyme genes for the binary classification problem and 14 enzyme genes for the ternary problem. It is noteworthy that all the 11 genes have literature support, showing that they each are associated with metastasis [17,18,19,20]. For the 14 genes, our functional analyses have revealed that they are mainly involved in sex hormone and xenobiotic metabolism, which makes sense as we have discovered that metastasized cancers have considerably elevated cholesterol metabolisms, leading to the production of sex hormones as well as mineral-and glucocorticoid (manuscript in preparation).…”
Section: Feature Selectionmentioning
confidence: 79%